Involvement of rest diastolic arterial pressure in autonomic heart rate recovery from exercise in normotensive men - Gomes, Rayana L. (2017)
OBJECTIVE: Rest arterial pressure has been shown to be associated with cardiovascular mortality. Autonomic heart rate control during recovery from exercise is estimated to detect changes in cardiovascular system, which may lead to cardiovascular diseases. We assessed the involvement of rest diastolic arterial pressure (DAP) on heart rate dynamics after exercise in normotensive physically active men.METHOD: We evaluated healthy physically active men aged 18 to 22 years old divided into two unequal groups: G1- rest DAP between 80 and 90 mmHg (N=11) and G2- rest DAP < 80mmHg (N=24). Volunteers performed physical exercise on a treadmill with intensity equivalent to 60% of Vmax. Heart rate recovery in the first (HRR1) and third (HRR3) minute after exercise were measured and heart rate variability (HRV) was examined in the time and frequency domain. Additionally, we performed the quantitative analysis of the Poincaré plot. HRV was recorded in the following phases: the 10-minute period before exercise, during exercise and the 60 minute period after exercise.RESULTS: We found no significant difference between G1 and G2 concerning HRV changes during exercise. The G2 group exhibited a delayed recovery of SDNN, RMSSD, RRTri, LF, HF, LF/HF, SD1 and SD2 indices during recovery from exercise. HRR1 and HRR3 was greater in the G2 group.CONCLUSION: Normotensive physically active men with DAP between 80 and 90 mmHg presented faster heart rate recovery and an accelerated recovery of heart rate autonomic control after aerobic exercise.